Alterations in the Abundance and Co-occurrence of Akkermansia muciniphila and Faecalibacterium prausnitzii in the Colonic Mucosa of Inflammatory Bowel Disease Subjects - Lopez-Siles, Mireia; Enrich-Capó, Núria; Aldeguer, Xavier; Sabat-Mir, Miriam; Duncan, Sylvia H.; Garcia-Gil, L. Jesús; Martinez-Medina, Margarita (Frontiers in Cellular and Infection Microbiology, 2018)
Akkermansia muciniphila and Faecalibacterium prausnitzii, cohabitants in the intestinal mucosa, are considered members of a healthy microbiota and reduction of both species occurs in several intestinal disorders, including inflammatory bowel disease. Little is known however about a possible link between the reduction in quantity of these species, and in which circumstances this may occur. This study aims to determine the abundances and co-occurrence of the two species in order to elucidate conditions that may compromise their presence in the gut. Loads of A. muciniphila, total F. prausnitzii (16S rRNA gene copies) and its two phylogroup were determined by quantitative polymerase chain reaction targeting specific regions of the 16S rRNA gene in colonic biopsies from 17 healthy controls (H), 23 patients with ulcerative colitis (UC) and 31 patients with Crohn’s disease (CD). Data were normalised to total bacterial 16S rRNA gene copies in the same sample. Prevalence, relative abundances and correlation analyses were performed according to type of disease and considering relevant clinical characteristics of patients such as IBD location, age of disease onset, CD behaviour, current medication and activity status. Co-occurrence of both species was found in 29% of H, 65% of UC and 29% of CD. Lower levels of total F. prausnitzii and phylogroups were found in subjects with CD, compared with H subjects (P≤0.044). In contrast, no differences were found with the regard to A. muciniphila abundance across different disease states,but CD patients with disease onset below 16 years of age featured a marked depletion of this species. In CD patients, correlation between A. muciniphila and total F. prausnitzii (ρ=0.362, P=0.045) was observed, and particularly in those with non-stricturing, non-penetrating disease behaviour and under moderate immunosuppressants therapy. Altogether, this study revealed that co-occurrence of both species differs between disease status. In addition, IBD patients featured a reduction of F. prausnitzii but similar loads of A. muciniphila when compared to H subjects, with the exception of those with early onset CD. Depletion of A. muciniphila in this subgroup of subjects suggests that it could be a potential biomarker to assist in paediatric CD diagnosis.